PEMANFAATAN LIMBAH TEMPURUNG KELAPA MENJADI BRIKET ARANG DI DESA UJUNG RAMBE, KECAMATAN BANGUN PURBA KABUPATEN DELI SERDANG - Sri Wahyuna Saragih; Rahimah; Friska Anggraini Barus; Busrizal Faisal; Adi Pranata; Toto Budianto; Yudha Febri Pramudiansyah; Muhammad Ferza; Budi Mulyara (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
Coconut plantations produce residue or waste that has not been utilized optimally. There are three types of waste produced by coconut plantations, namely solid waste, liquid waste and gas. One use of coconut solid waste is to use it as a renewable energy source or as an alternative fuel such as making charcoal briquettes. This potential illustration can be used as a waste processing innovation, which does not rule out the possibility of making society's economic cycle better. The aim of this research is to provide education to the people of Ujung Rambe Village, Bangun Purba District, Deli Serdang Regency about the use of coconut shell waste into charcoal briquettes. Providing education to the people of Ujung Rambe Village, Bangun Purba District, Deli Serdang Regency turns the process of making charcoal briquettes into a side income so that it can improve the community's economic benefits in daily life